Pengaruh Pengaplikasian Biosaka dan Daun Gamal Terhadap Pertumbuhan Tanaman Sawi (Brassica juncea L.): The Effect of Application of Biosaka and Gamal Leaves on the Growth of Mustard Plants (Brassica juncea. L) - Nensi, Sri Sulva; Jayadi, Muh.; Lias, Syamsul Arifin (Universitas Hasanuddin, 2025)
Technological developments in the agricultural sector are currently increasing for maximum production results. This encourages the use of chemicals or inorganic materials as nutrients for plants, especially mustard greens. Biosaka is a new form of innovation that is suitable for development because the basic materials used come from organic materials or green plants. This biosaka acts as an elicitor, not a fertilizer. This research aims to determine the effect of Biosaka and Gamal Leaves on the growth of mustard greens and is expected to reduce the use of chemicals. This research is divided into five main stages, namely: 1) Making Biosaka; 2) Incubation of Gamal Leaves; 3) Planting and maintaining mustard plants; 4) Application of Biosaka; and 5) Analyze and process data using a Completely Randomized Design (CRD) with 10 levels of treatment combinations (biosaka 4 levels of treatment and gamal leaves 3 levels of treatment). In the parameters of plant height, number of leaves, pH, C-Organic, and N-total, the K2G1 treatment (3 ml of biosaka + 2 liters of H2O + 25 grams of gamal leaves) was the treatment with the best results. Meanwhile, for the parameters of fresh weight, leaf length and Cation Exchange Capacity (CEC), the K3G2 treatment (4.5 ml of biosaka + 2 liters of H2O + 50 grams of gamal leaves) showed the best treatment. The K3G2 treatment was the treatment with the best results with a value of 35.67 grams with a percentage increase of 2.32% from the control treatment. Based on the results of research on the application of Biosaka and Gamal Leaves, it shows a very real influence in the interaction test of the two factors, which means there is an influence on the plants after being treated.